INVESTIGATING GENDER GAP IN METACOGNITIVE READING STRATEGY: UNEARTHING PRACTICAL CHALLENGES IN ONLINE EFL READING - Radina Anggun Nurisma; Yazid Basthomi (Wiralodra English Journal, 2025)
Despite the growing use of online reading in higher education, particularly among EFL learners, limited study has examined how students differ in their use of reading strategies and the specific challenges they face in online context. Most studies address online reading in general terms, but few examine gender-based perceptions and strategic behaviors in online environments. This study aims to fill the gap by examining the application of metacognitive strategies in online reading focusing on gender differences and the challenges students encounter. A mixed method was employed, involving 100 undergraduate students from non-English departments. Data were gathered using the Online Reading Strategies Inventory (ORSI) and open-ended questionnaires. Findings revealed that both male and female students reported moderate use of metacognitive strategies, with no significant difference in overall strategy selection. However, a gender-related gap was observed in the utilization of support strategies. Additionally, students identified several challenges, including limited engagement with digital features, low literacy skills, and a lack of effective strategy use. The results offer substantial pedagogical implications for English language teaching, emphasizing the need to address students’ difficulties in online reading and to train them in diverse metacognitive strategies to strengthen their reading comprehension, particularly in online contexts.